2009
DOI: 10.1016/j.ejcts.2009.01.038
|View full text |Cite
|
Sign up to set email alerts
|

A newly designed thorax support vest prevents sternum instability after median sternotomy☆

Abstract: The use of the Posthorax sternum vest shows a favourable outcome to prevent sternum instability after cardiac surgery. There was one reoperation in patients treated with this sternum vest compared to 16 in the control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 23 publications
2
26
2
6
Order By: Relevance
“…These clinical improvements may be attributed to the improved sternum stability in group A that is provided by the Posthorax support vest without limitation on breathing and this can be translated in better patient comfort and mobility and lower incidence of mechanically induced sternum complications, but quite importantly in our “economic conscious” age can mean lower associated healthcare costs. Our findings are supported by other randomized studies from the literature [9, 18, 19]. However, these studies are multicentric and included infective and non-infective sternal complications and furthermore they did not do an extensive subgroup analysis on patients with a high risk for sternal complications.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These clinical improvements may be attributed to the improved sternum stability in group A that is provided by the Posthorax support vest without limitation on breathing and this can be translated in better patient comfort and mobility and lower incidence of mechanically induced sternum complications, but quite importantly in our “economic conscious” age can mean lower associated healthcare costs. Our findings are supported by other randomized studies from the literature [9, 18, 19]. However, these studies are multicentric and included infective and non-infective sternal complications and furthermore they did not do an extensive subgroup analysis on patients with a high risk for sternal complications.…”
Section: Discussionsupporting
confidence: 86%
“…The Posthorax vest is the latest technological generation of sternum support corsets [18]. It has been designed to stabilize the sternum following sternotomy so as to avoid excessive stress on the sternum wires during bone healing [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Devices for external compression of the thorax to prevent or treat sternal instabilities have been systematically investigated in only a few studies, but have shown promising results [4]. Relatively rigid 'corset-like' constructions can, as we have occasionally observed, easily slip out of place, particularly on patients who are obese, and cause skin irritations at the edges of the material due to bulging skin.…”
Section: Resultsmentioning
confidence: 99%